2017
DOI: 10.3390/nu9070781
|View full text |Cite
|
Sign up to set email alerts
|

Fat Taste Sensitivity Is Associated with Short-Term and Habitual Fat Intake

Abstract: Evidence suggests individuals less sensitive to fat taste (high fat taste thresholds (FTT)) may be overweight or obese and consume greater amounts of dietary fat than more sensitive individuals. The aims of this study were to assess associations between FTT, anthropometric measurements, fat intake, and liking of fatty foods. FTT was assessed in 69 Australian females (mean age 41.3 (15.6) (SD) years and mean body mass index 26.3 (5.7) kg/m2) by a 3-alternate forced choice methodology and transformed to an ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 30 publications
3
50
1
Order By: Relevance
“…Until the first decade of the 21st century, it was assumed that the sense of taste included 5 main flavors: sweet, salty, sour, bitter, and glutamate [6][7][8]. Studies in the last decade also documented the important role of perception of fat taste (character) in animal and human behavior [9][10][11][12][13]. The ability to perceive flavors begins in the uterus through the amniotic fluid as well as breast milk, along with the development and early functioning of the taste and olfactory system [14].…”
Section: Introductionmentioning
confidence: 99%
“…Until the first decade of the 21st century, it was assumed that the sense of taste included 5 main flavors: sweet, salty, sour, bitter, and glutamate [6][7][8]. Studies in the last decade also documented the important role of perception of fat taste (character) in animal and human behavior [9][10][11][12][13]. The ability to perceive flavors begins in the uterus through the amniotic fluid as well as breast milk, along with the development and early functioning of the taste and olfactory system [14].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest concentration in this study was higher than that of a study by Constanzo, et al in which the whole mouth method was used. 5 In that study, most of the subjects were able to recognize the tastes in the lowest concentrations of the taste solutions. The lowest concentrations in this study were 0.31 mg/ml to 59.75 mg/ml higher than those in the Constanzo et al study.…”
Section: Discussionmentioning
confidence: 92%
“…4 Individuals with decreased taste sensitivity may change their dietary habits by consuming excessive amounts of tastants. 5 Such disturbance-associated dietary alterations can lead to various diseases, including obesity and diabetes mellitus. 6 Vitamins play an important role in maintaining the integrity of the oral mucosa, including the tongue papillae, and a deficiency in vitamin B 12 causes the tongue papillae to atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the response to fat stimulation in the oral cavity was previously considered to rely largely on olfactory, textural, and post-ingestive cues. However, fatty acid taste (the taste of free fatty acids, but not triacylglycerides) has recently been suggested as a new basic taste (Costanzo et al 2017). In fact, accumulating evidence indicates that long-chain fatty acids, such as oleic acid (OA, C 18 H 34 O 2 , a monounsaturated fatty acid found in many vegetable and animal oils), elicits a unique, perceptive sensation at concentrations relevant to the modern food supply (Running et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the contradictory results are largely unknown, and more studies in this area are essential for a better understanding of the topic (Martínez-Ruiz et al 2014). On the other hand, several studies proposed that fatty acid taste sensitivity is associated with fatty food consumption (Stewart et al 2010(Stewart et al , 2011 or other eating habits, including satiety after food intake (Asano et al 2016;Costanzo et al 2017), suggesting the existence of unique regulatory mechanisms of OFS in the body. In addition, an intervention study showed that fat taste threshold increased when participants were exposed to a low-fat diet over a four-week period.…”
Section: Introductionmentioning
confidence: 99%